PROJECT DEVELOPMENT METHODOLOGY FOR COMPUTER SCIENCE PROJECTS USING AN OBJECT-ORIENTED APPROACH - Rosziati Ibrahim (2014)
This book introduces project development methodology for computer science projects using object-oriented approach. The object-oriented approach simplifies and reinforces the learning process based on the notion of object. This book consists of 7 chapters. Chapter 1 attempts to introduce the project proposal and discuss the contents within the project proposal. Chapter 2 introduces the first step in doing the project which is literature reviews.  Chapter 3 covers topics on requirements analysis phase which is the first phase in object-oriented software development life cycle (OOSDLC). Chapter 4 discusses the second phase in OOSDLC which is the design phase. Chapter 5 discusses the third phase in OOSDLC that is the implementation phase and Chapter 6 discusses the fourth phase in OOSDLC which is the testing phase. Finally, Chapter 7 discusses the format for the report writing during writing up of the thesis as well as the format for the presentation style for the purpose of presenting the thesis during viva session.